2017
DOI: 10.1016/j.cub.2017.02.031
|View full text |Cite
|
Sign up to set email alerts
|

A Large and Consistent Phylogenomic Dataset Supports Sponges as the Sister Group to All Other Animals

Abstract: Resolving the early diversification of animal lineages has proven difficult, even using genome-scale datasets. Several phylogenomic studies have supported the classical scenario in which sponges (Porifera) are the sister group to all other animals ("Porifera-sister" hypothesis), consistent with a single origin of the gut, nerve cells, and muscle cells in the stem lineage of eumetazoans (bilaterians + ctenophores + cnidarians). In contrast, several other studies have recovered an alternative topology in which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
476
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 481 publications
(532 citation statements)
references
References 52 publications
27
476
2
1
Order By: Relevance
“…In the case of the metazoan controversy, analyses employing site-homogeneous models of protein evolution with partitioning (a different model for each gene) tend to recover ctenophores as the sister branch ([2, 3, 7, 32, 33, 3840], but see [35, 42]). In contrast, analyses employing site-heterogeneous models (and in particular the CAT model [47]) typically recover sponges as the sister branch ([3437, 41, 42], but see [38, 40, 48]).…”
Section: Enter the Phylogenomics Eramentioning
confidence: 99%
“…In the case of the metazoan controversy, analyses employing site-homogeneous models of protein evolution with partitioning (a different model for each gene) tend to recover ctenophores as the sister branch ([2, 3, 7, 32, 33, 3840], but see [35, 42]). In contrast, analyses employing site-heterogeneous models (and in particular the CAT model [47]) typically recover sponges as the sister branch ([3437, 41, 42], but see [38, 40, 48]).…”
Section: Enter the Phylogenomics Eramentioning
confidence: 99%
“…In addition, the adult staurozoan body plan includes features common to both the polyp and medusa stages of other cnidarians, thus adding to their phylogenetic significance (Collins 2002(Collins , 2010Miranda, et al 2016a;Miranda, et al 2013;Miranda, et al 2016b). The phylogenetic position of staurozoans relative to other medusozoan lineages remains controversial and recent hypotheses (Kayal, et al 2013;Simion, et al 2017;Zapata, et al 2015) present different implications for the evolution of medusozoan body plans ( Figure 1F). Analyses of rDNA, life history and anatomical features have suggested that Staurozoa is the sister lineage to the remainder of Medusozoa (Collins 2002;Van Iten 1992).…”
Section: Introductionmentioning
confidence: 99%
“…First, the deep phylogeny of animals is unresolved. Currently, there are two competing theories placing either sponges 48 or ctenophores 49 as the earliest-branching lineage. Second, the sequences of Nme genes and proteins often do not contain sufficient phylogenetic signal to reconstruct their evolutionary history at the base of the animal tree.…”
Section: Discussionmentioning
confidence: 99%